Pengaruh Beban Kerja dan Disiplin Kerja Terhadap Turnover Intention Guru dan Karyawan pada Unit Sekolah di Yayasan Masjid Al Ikhlas - Arinda Tria Destiani; Ety Nurhayaty (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Al Ikhlas Mosque Foundation has a Turnover intention percentage value above 10% in several years during the period 2019 to 2023. Meanwhile, based on the prariset, it was found that the workload variable was the most selected variable and followed by the work discipline variable with a percentage value of only 20% in the period 2020 to 2023. The purpose of this study is to determine the effect of workload and work discipline on Turnover intention of teachers and employees in the school unit at the Al Ikhlas Mosque Foundation (YMAI), Jakarta. This study uses a quantitative descriptive method with data collection techniques in the form of documentation, and a questionnaire in the form of a Likert scale. The population used was 95 respondents and in withdrawing samples using saturated samples. Furthermore, the data were tested for validity and reliability and carried out normality tests, Heteroscedasticity tests, multicollinearity tests.  Data analysis was carried out using multiple linear regression equation tests with the results Y = -0.456 + 0.254X1 + 0.667X2 which shows that workload and work discipline affect Turnover intention. Furthermore, partially workload affects Turnover intention by 63.2% and work discipline affects turnover intention by 7.47%. Meanwhile, simultaneously workload and work discipline affect turnover intention by 75.8%.